How Emotions Influence the Psychophysical Well-being of Children - Manuela Valentini; Roberta Giontarelli (Lubelski Rocznik Pedagogiczny, 2022)
Introduction: The current work, through a strict review of the literature, is aimed at highlighting how emotions, physical activity and a healthy diet can affect psychophysical well-being in childhood, particularly between the ages of 3–12.